2022
DOI: 10.1021/acs.jafc.2c03050
|View full text |Cite
|
Sign up to set email alerts
|

Structure–Activity Relationship (SAR) of Flavones on Their Anti-Inflammatory Activity in Murine Macrophages in Culture through the NF-κB Pathway and c-Src Kinase Receptor

Abstract: Flavones benefit human health through their anti-inflammatory activity; however, their structure−activity relationship is unclear. Herein, we selected 15 flavones with the same backbone but different substituents and systematically assessed their antiinflammatory activities in RAW 264.7 regarding cellular-Src kinase (c-Src) affinity, suppression of IκBα phosphorylation, inhibition of nitric oxide (NO) and inducible nitric oxidase (iNOS) production, and downregulation of genes of proinflammatory cytokines inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Numerous studies have attempted to explore the structure–activity relationship of flavonoids. However, no clear conclusion has been reached so far, which may be due to insufficient investigation on the influence mechanism under specific systems. The results of our entire research indicated that for compounds with inherent lipid-lowering activity, the bioavailability, which manifests as stability and cellular uptake ratio, is the crucial condition that determines whether compounds can exert efficacy in cell experiments.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have attempted to explore the structure–activity relationship of flavonoids. However, no clear conclusion has been reached so far, which may be due to insufficient investigation on the influence mechanism under specific systems. The results of our entire research indicated that for compounds with inherent lipid-lowering activity, the bioavailability, which manifests as stability and cellular uptake ratio, is the crucial condition that determines whether compounds can exert efficacy in cell experiments.…”
Section: Discussionmentioning
confidence: 99%
“…The cellular inflammation induction model refers to previous research [ 32 ], RAW 264.7 mouse macrophages were cultured in DMEM containing fetal bovine serum, penicillin, and streptomycin (37 °C, 5% CO 2 ). Change the medium every 1–2 days and pass the passage every 2 days.…”
Section: Methodsmentioning
confidence: 99%
“…Human peripheral blood mononuclear cells (PBMCs) and TNBS-induced colitis rat IL-10, transforming growth factor (TGF)-β1, IL-2p70, forkhead box protein 3 (Foxp3) and Treg production [28,29] Caco-2 cells and TNBS-induced colitis mice IL-10 IL-12, interferon-γ (IFN-γ), IL-8 and NF-κB activation [19] DSS colitis C57BL/6 mice Claudin-1 and claudin-2 expressions Weight and colon length [30] Dinitrobenzene sulfonic acid (DNBS) -induced colitis mice…”
Section: Faecalibacterium Faecalibacterium Prausnitziimentioning
confidence: 99%